قصيدة "أمن أم أوفى" لزهير بن أبي سلمى (دراسة نقدية في عناصرها الأدبية) - Lalu Turjiman Ahmad (Ulumuna, 2007)
Literary, through its many forms, is found as a mirror of life, since it contains values and wisdoms of time and place where it is produced. Qashîdah (Arabic poetry) of Zuhayr ibn Abî Sulmâ as a kind of literary works can be considered as representation of so many other works uncovering pre-Islamic Arabic wisdom. Through literary critique, this article highlights intrinsic elements of qashîdah “A-Min Ummi Aufâ” of Zuhayr ibn Abî Sulmâ. Under the theme of hikmah (wisdom) contained in this qashîdah, ideas are dominant elements. The ideas expressed by Zuhayr deserved admiration of biggest critic of Prophet Contemporaries period, Umar ibn Khattab. Moral messages implied and expressed through its beautiful Ianguage style and high level of imagination; become one of other reasons why this qashîdah still get attention hitherto.